Preparation and characterisation of electrospun silica nanofibres. (8th December 2014) - Talebian, S.; Afifi, A. M.; Hatami, M.; Bazgir, S.; Khanlou, H. M.
<x content-type="archive" xml:space="preserve">Abstract</x> In this study, the silica electrospun nanofibres were fabricated using silica sol containing tetraethylorthosilicate, polyvinylpyrrolidone and butanol (solvent). The perfect concentration for silica sol to undergo the electrospinning was found to be 0·095 gr(pvp)/mL (butanol, tetraethyl orthosilicate), where the tetraethyl orthosilicate/butanol volume ratio was 3:2. Later with the intention of achieving the silica nanofibres, the electrospun samples afterwards were put in a furnace at 700°C for 3 hours. After that the morphological studies on the fibres before and after the thermal treatment were done employing the scanning electron microscopy. The results showed that fibre diameter before thermal treatment fits the micrometre scale, while it decreases dramatically to the 260–360 nm range when it goes through the thermal stage. Furthermore, Fourier transform infrared spectroscopy and energy-dispersive X-ray spectroscopy spectrums proved that polyvinylpyrrolidone and butanol were removed from the fibres after calcination and that the silica nanofibres were fabricated.